Exploring Other-Than-Human Identity: Religious Experiences in the Life-Story of a Machinekin - Stephanie C. Shea (Religions, 2020)
The term Machinekin denotes a sub-group of a larger Internet subculture known as Otherkin: while recognizing they have a human body and mind, these people nevertheless identify as being other-than-human. Machinekin therefore identify as a machine of some sort. In attempting to study this subculture, qualitative psychological research methods are used, combined with digital ethnography. Postmodern theories of identity formation, such as narrative identity, and especially McAdams’s seven features of the life-story, are implemented in order to interpret how Neve, a Machinekin, came to understand his non-human identity, as well as the role religion has played in his identity configuration. Additionally, the function of religion as it applies to finding meaning in conflicting circumstances is also considered. Neve’s experiences can be seen as an example of how religion and identity are interrelated, with the story showing what key events led Neve to look to religion for answers to difficult questions that arose in his early years. The interpretation of these events eventually led to an understanding of Neve’s lived experiences, and to a sense of purpose for his life. It also demonstrates how Machinekin challenge attitudes surrounding identity and the boundaries of what constitutes a “person”.